2013
DOI: 10.2511/027494813807046926
|View full text |Cite
|
Sign up to set email alerts
|

Review of Experimental Research on Academic Learning by Students with Moderate and Severe Intellectual Disability in General Education

Abstract: A review of the literature on academic learning in general education settings for students with moderate and severe intellectual disability was conducted. A total of 17 experimental studies was identified and evaluated using quality indicators for single-case design research. Studies that met or met with reservation the criteria established for quality research were used to determine the evidence base of the instructional strategies described in the literature. The review found embedded instruction trials usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 34 publications
2
58
0
1
Order By: Relevance
“…The research on peer support provided for students with SMD in inclusive PE has been minimal. However, the results from special education studies done in classrooms (Greenwood et al, 2002;Hudson et al, 2013;Yun -Ching, Carter, & Sisco, 2013) are in line with adapted physical education studies demonstrating more frequent interactions between peers and students with SMD during peer tutoring than during teacher instruction (Klavina, 2008;Klavina & Block, 2008).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The research on peer support provided for students with SMD in inclusive PE has been minimal. However, the results from special education studies done in classrooms (Greenwood et al, 2002;Hudson et al, 2013;Yun -Ching, Carter, & Sisco, 2013) are in line with adapted physical education studies demonstrating more frequent interactions between peers and students with SMD during peer tutoring than during teacher instruction (Klavina, 2008;Klavina & Block, 2008).…”
mentioning
confidence: 72%
“…Several studies have indicated that peer tutoring can be used as effective instructional accommodation to improve academic outcome of students with disabilities (Houston-Wilson et al, 1997;Lieberman et al, 1997Lieberman et al, , 2000Murata & Jansma, 1997) and increase interactions between peers with and without severe disabilities (Klavina & Block, 2008) in inclusive PE. As indicated above, regarding peer tutoring for students with SMD, many special education studies have explored peer support instructional arrangements to increase students' with SMD engaged time and academic success in classroom setting (Hudson, Browder, & Wood, 2013;Okilwa, 2010). The research on peer support provided for students with SMD in inclusive PE has been minimal.…”
mentioning
confidence: 99%
“…Research supports the use of embedded instruction for teaching students with severe disabilities (Barnes & Whinnery, 2002Hudson et al, 2013). When planning embedded instruction, practitioners identify existing routines within the school day in which to incorporate supplemental instruction to teach priority skills and remediate skill deficits.…”
Section: Mrsmentioning
confidence: 99%
“…Embedded instruction has been used to successfully teach targeted skills within existing activities and routines during the school day (Hudson, Browder, & Wood, 2013). This strategy allows educational teams to insert teaching trials into the ongoing schedule without breaking the flow of the routine or activity.…”
Section: Embedded Instructionmentioning
confidence: 99%
“…However, they have difficulties in developing these basic academic skills. Effective procedures are needed to teach academic content to these students (Hudson, Browder, & Wood, 2013). However, since special education support services are limited and existing teaching is not adequate, these students cannot achieve basic academic skills (Akçamete, Gürgür, & Kış, 2003;Kalkan & Özmen, 2013;Özbay, Özmen, Tuncer, & Altunay, 2007).…”
mentioning
confidence: 99%